2013
DOI: 10.1016/j.sleep.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter evaluation of oral pressure therapy for the treatment of obstructive sleep apnea

Abstract: Objective We aimed to evaluate the impact of a novel noninvasive oral pressure therapy (OPT) (Winx®, ApniCure) system on polysomnographic measures of sleep-disordered breathing, sleep architecture, and sleep stability in obstructive sleep apnea (OSA). Subjects and methods A 4-week, multicenter, prospective, open-label, randomized, crossover, first-night order of control vs treatment, single-arm trial was conducted in five American Academy of Sleep Medicine (AASM) – accredited sleep clinics and one research l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Nonsurgical treatments include continuous positive airway pressure (CPAP), oral appliances (i.e. mandibular advancement devices) [Clark et al 1996;Ferguson et al 2006], and nasal appliances [Colrain et al 2008]. Pharmacotherapy has had a very limited role as a primary treatment of OSA [Jayaraman et al 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Nonsurgical treatments include continuous positive airway pressure (CPAP), oral appliances (i.e. mandibular advancement devices) [Clark et al 1996;Ferguson et al 2006], and nasal appliances [Colrain et al 2008]. Pharmacotherapy has had a very limited role as a primary treatment of OSA [Jayaraman et al 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The nasal expiratory positive airway pressure (EPAP) (Provent sleep therapy, Ventus Medical Inc., USA) is a unidirectional flow-resistant device aimed at regulating airflow through the nostrils (expiratory flow resistance without any inspiratory resistance). Different studies have been conducted to assess its effectiveness [55,56]. Significantly (p<0.001) reduction in AHI compared with initial PSG were reported in mild, moderate and severe OSAHS patients.…”
Section: Osahs Treatmentmentioning
confidence: 99%
“…Colrain et al assessed the safety and effectiveness of the Winx device in a population composed of mild-to-severe OSAHS patients. Clinically significant improvement in AHI, sleep quality and continuity, and daytime sleepiness were reported [57]. Nevertheless, further work is needed to confirm the effectiveness of such devices as reliable alternative to conventional CPAP therapy.…”
Section: Osahs Treatmentmentioning
confidence: 99%
“…Alternative therapeutic devices that could replace CPAP for short or long periods are therefore required. Some previous studies have reported oral or nasopharyngeal appliances as non-surgical alternatives to CPAP for OSA patients who do not tolerate CPAP treatment [12][13][14][15][16][17][18]. Although the concept of nasopharyngeal tube insertion to maintain airflow through the upper airway during sleep was proposed in the 1980s and has been reviewed before [7,12,18], such devices are not currently in common use.…”
Section: Introductionmentioning
confidence: 99%